Dos especies nuevas y nuevos registros de los genero Maxilata y Anatinothrips (Thysanoptera: Phlaeothripidae) - Soto Rodríguez, Gerardo A.; Retana Salazar, Axel P. (Instituto de Ecología, A.C., 2000)
Two new species of Phlaeothripidae are described for the genus Maxillata and Anactinothriops. The species allani can be distinguished by the position of the stylets and the antennal coloration. On the other hand, the species davidi is characteristic by the length of the mid-dorsal setae on the head and the coloration of the antennal segments. This is the first record of both genus in Costa Rica.